(untitled) (Texas Journal of Engineering and Technology, 2025)
This paper examines strategies for identifying, conserving and optimising resource use in industrial enterprises. The study focuses on approaches to conserving energy, raw materials and waste in manufacturing, processing and heavy industries, and integrated conservation systems yield an average increase in resource efficiency of 23–38% compared to isolated interventions, with significant differences across industrial sectors